E-023 Consecutive Endovascular Treatment of Ruptured Very Small (<3 mm) Anterior Communicating (ACom) Artery Aneurysms: A Single Center Experience. (26th July 2014) - Asif, K; Teleb, M; Sattar, A; Lazzaro, M; Fitzsimmons, B; Lynch, J; Zaidat, O
Abstract : Background: The anterior communicating (ACom) artery is the most common location of cerebral aneurysms harbouring upto 30–37% of all treated aneurysms. Amongst all ruptured aneurysms, the proportion of patients with very small aneurysms ranges from 12–18%. Treatment of very small aneurysms (<3 mm) of the anterior communicating artery presents a unique set of challenges for both surgical as well as endovascular techniques. Objective: To report the immediate and long-term clinical as well as radiographic outcomes of consecutive patients with ruptured very small anterior communicating artery (ACOM) aneurysms treated with endovascular technique. Methods: A prospectively maintained single institution neuro-endovascular database was accessed to identify consecutive cases of very small (<3 mm) ruptured ACom aneurysms treated endovascularly between 2006 and 2013. Clinical, demographic, radiographic, and procedural data were retrospectively obtained through chart review. Results: A cohort of 20 consecutive patients with ruptured very small (<3 mm) ACom artery aneurysms were treated endovascularly including 13 females and 7 males with a mean age of 58.4 ± 12.9 yrs. Average maximum aneurysm diameter was 2.66 (± 0.41) mm. Hunt-Hess grade 1–3 for 14 (70%) patients and 4 for 6 (30%) patients. Dome to neck ratio was less than 2 for 13 (65%) of the aneurysms. Four (20%) aneurysms were bilobed. Aneurysm projection was antero-superior in 11 (55%), antero-inferior in 6 (30%) and postero-superior in 3 (15%). Primary coiling was performed for 16 (80%) aneurysms and balloon assistance was used for 4 (20%). Complete aneurysm occlusion was achieved for 17 (85%) aneurysms and near complete for 3 (15%) aneurysms. There were no symptomatic peri-procedural complications. Intra-operative perforation (IOP) occurred in 2 (10%) patients without any clinical worsening or need for an external ventricular drain. Thromboembolic event (TEE) occurred in 1 (5%) patient without clinical worsening or new radiologic infarct. Median clinical follow up was 12 (± 14.1) months and median imaging follow up was 12 (± 18.4) months. There were no instances of re-bleeding during follow up. At the 3 month clinic follow up, modified Rankin scale was 6 for one patient related to anaplastic astrocytoma. Of all the surviving 19 patients, post treatment clinical status either improved or remained stable. Recanalization with a neck residual occurred in two (10%) aneurysms and both were retreated with additional primary coiling and stent assistance. Conclusion: Endovascular treatment of very small ACom aneurysms can be performed with acceptable rates of complications and recanalization. Robust conclusions can be drawn only after further evaluation with larger number of patients and longer follow-up. Disclosures: K. Asif: None. M. Teleb: None. A. Sattar: None. M. Lazzaro: None. B. Fitzsimmons: None. J. Lynch: None. O. Zaidat: None.